2020
DOI: 10.1002/ejoc.202001132
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Naphthols: Preparations, Applications, and Reactions

Abstract: Substituted naphthols (SNs) are an important class of chemical compounds present in many natural and synthetic products with biological and pharmaceutical activities. Moreover, the naphthol skeleton has been employed as a starting material for the development of drug molecules and natural products. Thus, different synthetic methods to access naphthol cores have been reported using diverse starting materials and chemical strategies. This review article describes literature on synthetic methodologies of substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Naphthols as critical skeletons exist in many biologically active compounds (Figure ). Xanthones, possessing dibenzo-γ-pyrone heterocyclic scaffold, are the privileged structures found as secondary metabolites in diverse organism, and exhibit interesting bioactivities (Figure ). Thus, they may be considered as potentially promising structures for drug development.…”
mentioning
confidence: 99%
“…Naphthols as critical skeletons exist in many biologically active compounds (Figure ). Xanthones, possessing dibenzo-γ-pyrone heterocyclic scaffold, are the privileged structures found as secondary metabolites in diverse organism, and exhibit interesting bioactivities (Figure ). Thus, they may be considered as potentially promising structures for drug development.…”
mentioning
confidence: 99%
“…We report here that these reactions provide a unique method for the synthesis of substituted 1-naphthols, which constitute an important class of bicyclic compounds widely found in many natural and synthetic products. 10 Furthermore, 1-naphthols have been used as building blocks in organic synthesis to access complex organic compounds. 11…”
mentioning
confidence: 99%
“…While numerous aromatic compounds have been synthesized via redox-neutral transition-metal-catalyzed cycloadditions of unsaturated acyclic compounds such as α,ωdiynes, 17 the synthesis of 1-naphthol derivatives using this method remains rare, 18 despite substituted 1-naphthols being an important class of structural motifs found in many bioactive natural products and pharmaceuticals. 19 Herein, we report a novel cobalt/photoredox dual-catalysis-enabled cascade cyclization of 1,6-diynyl esters to furnish 1-naphthol derivatives. We found that a vinylallene is generated by formal 1,8-acyloxy migration via β-oxygen elimination of a cobaltacyclopentadiene intermediate, which has not, to the best of our knowledge, been reported to date (Scheme 1C).…”
mentioning
confidence: 99%
“…Recently, we have reported an asymmetric [2 + 2 + 2] cycloaddition of enediynes mediated by cobalt/photoredox dual catalysis to furnish enantioenriched tricyclic molecules (Scheme B). , During this study, we were surprised to observe that the use of an ester-tethered enediyne produced a 1-naphthol derivative selectively, albeit in low yield, while the tricyclic [2 + 2 + 2] cycloadduct was not detected. While numerous aromatic compounds have been synthesized via redox-neutral transition-metal-catalyzed cycloadditions of unsaturated acyclic compounds such as α,ω-diynes, the synthesis of 1-naphthol derivatives using this method remains rare, despite substituted 1-naphthols being an important class of structural motifs found in many bioactive natural products and pharmaceuticals . Herein, we report a novel cobalt/photoredox dual-catalysis-enabled cascade cyclization of 1,6-diynyl esters to furnish 1-naphthol derivatives.…”
mentioning
confidence: 99%